Dynamics of Actors and Stakeholders in the Formation of Public Policy Arguments: A Review through the Narrative Policy Framework and the Advocacy Coalition Framework - Ridho Marnas (Internasional Journal of Politics and Public Policy, 2026)
The formulation of public policy is a dynamic process shaped by interactions among policy actors and stakeholders who possess different interests, resources, and levels of influence. However, previous studies have largely examined policy actors, stakeholder participation, policy narratives, and advocacy coalitions separately, leaving limited understanding of how these dimensions interact in shaping policy arguments. This study aims to analyze the influence of actors and stakeholders on the formation of public policy arguments through an integrative review using the Narrative Policy Framework (NPF) and the Advocacy Coalition Framework (ACF). The research employed a qualitative approach using a systematic literature review. Data were collected from 35 scientific journal articles and 8 academic books published between 2020 and 2026, obtained from Google Scholar, Scopus, SINTA, and GARUDA. The data were analyzed using thematic content analysis by identifying patterns related to policy actors, stakeholder roles, policy narratives, and advocacy coalitions. The findings reveal that formal actors, including government institutions and bureaucracies, dominate policy argumentation through institutional authority, while informal actors such as academics, media, civil society organizations, and interest groups contribute by producing evidence, shaping public opinion, and conducting advocacy. The Narrative Policy Framework demonstrates that policy actors strategically construct narratives through settings, characters, plots, and moral messages to legitimize policy preferences and mobilize public support. Meanwhile, the Advocacy Coalition Framework explains that actors sharing similar policy core beliefs establish advocacy coalitions to strengthen collective arguments and influence policy outcomes. The study concludes that public policy arguments emerge from the interaction of actor power, stakeholder interests, narrative construction, and advocacy coalition dynamics. Integrating NPF and ACF provides a more comprehensive analytical framework for understanding policy argumentation and offers valuable insights for developing more inclusive and evidence-based policymaking.